2018
DOI: 10.1038/s41598-017-18162-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Vortices as Efficient Nano Heaters in Magnetic Nanoparticle Hyperthermia

Abstract: Magnetic vortices existing in soft magnetic nanoparticles with sizes larger than the single-domain diameter can be efficient nano-heaters in biomedical applications. Using micromagnetic numerical simulation we prove that in the optimal range of particle diameters the magnetization reversal of the vortices in spherical iron and magnetite nanoparticles is possible for moderate amplitudes of external alternating magnetic field, H0 < 100 Oe. In contrast to the case of superparamagnetic nanoparticles, for the vorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 54 publications
2
49
0
2
Order By: Relevance
“…In addition, according to their superparamagnetic property (hc $ 0), most of the particles contains only single domain. [35][36][37] Figure S3 shows as-prepared colloid of MNPs and the same sample after remaining for 20 days. As it was clear, just after a few minutes of sonication, these nanoparticles have been fully dispersed in aqueous media and the mixture was stable for several days.…”
Section: Characterizations Of Mnpsmentioning
confidence: 99%
“…In addition, according to their superparamagnetic property (hc $ 0), most of the particles contains only single domain. [35][36][37] Figure S3 shows as-prepared colloid of MNPs and the same sample after remaining for 20 days. As it was clear, just after a few minutes of sonication, these nanoparticles have been fully dispersed in aqueous media and the mixture was stable for several days.…”
Section: Characterizations Of Mnpsmentioning
confidence: 99%
“…Magnetic NPs, such as superparamagnetic iron oxide, are another additive agent that has shown great promise towards the advancement of non-invasive and safe cancer therapy through targeted magnetically-stimulated ablation of tumor cells, which is referred to as hyperthermia (62,63). A recent study found that hyperthermic efficiency was affected by the shape of the iron oxide NPs, with square shapes generating more heat energy and able to be synthesized at smaller sizes than spheres (63).…”
Section: Theranostics For Tumor Ablation In Cancer Patientsmentioning
confidence: 99%
“…An extremely quick alternating external magnetic field is applied to magnetic NPs that have arrived at the tumor site, which causes their magnetic moments to alternate at a frequency that generates enough heat to ablate the cancer cells (62). Magnetic NPs also confer theranostic capabilities because most act as either T1 or T2 contrast agents for MRI (63). This ability to image the NPs in vivo allows the tumor cells to be precisely located and targeted in a manner that avoids inducing cytotoxic effects towards healthy cells (63).…”
Section: Theranostics For Tumor Ablation In Cancer Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously developed a magnetic nanoparticle (MNP) hyperthermia platform and validated its capacity to target and substantially reduce the viability of bacterial pathogens using an in vivo mouse model of Staphylococcus aureus (S. aureus) wound infection [9]. The principle of this method is to induce a localized increase in temperature in bacterial cells by targeted activation of MNPs with an externally applied energy source of high frequency alternating magnetic field (AMF) [10][11][12]. However, the use of MNP/AMF hyperthermia alone is still limited due to potential thermal damage to the host tissue, since it typically requires the application of MNP/AMF at higher thermal doses for complete eradication of bacterial pathogens.…”
Section: Introductionmentioning
confidence: 99%